THE CONCEPT OF INDIVIDUALIZATION IN 4.0 ERA STUDENTS - Yurike Bala; Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
This article discusses the concept of individualization for students in the Industrial Revolution 4.0 era. Higher education is currently faced with new challenges caused by technological developments and social transformation. The concept of individualization is an important key in ensuring that students can develop their unique potential optimally. This article discusses the impact of the Industrial Revolution 4.0 on higher education and outlines individualization strategies that can be implemented to improve the student learning experience Individualization in the 4.0 era refers to the concept of giving freedom to students to develop their unique potential according to their interests, talents and career goals. In a learning environment characterized by the integration of technology, students are encouraged to choose study paths that suit technological developments, while building distinctive personal and professional skills. Through this approach, students can become individuals who are adaptive, creative, and ready to face the complex demands of the world of work in the 4.0 era. Individualization in students in the 4.0 era includes the development of unique personal and professional skills according to their interests, talents, and career goals. Era 4.0 emphasizes technology integration, creativity and adaptability. Students need to explore their own potential, choose an appropriate study path, and engage in learning that is collaborative and oriented. The Industrial Revolution 4.0 has created a deep transformation in almost all aspects of life, including the world of education. Higher education, as the main support for human resource development, cannot escape the impact of this change.